Midfoot Derotational Osteotomy for Ankylosing Inversion Deformity in Patients with Rheumatoid Arthritis: A Report of 3 Cases. Issue 1 (26th January 2022) - Etani, Yuki; Hirao, Makoto; Ebina, Kosuke; Kunugiza, Yasuo; Noguchi, Takaaki; Tsuboi, Hideki; Tsuji, Shigeyoshi; Okada, Seiji; Hashimoto, Jun
Abstract : Case: Ankylosing midfoot inversion deformities in 3 patients with rheumatoid arthritis (RA) treated by midfoot derotational osteotomy to remove the pain due to excessive loading of the fifth metatarsal base and to obtain the plantigrade position are presented. All cases achieved sufficient correction and good clinical and radiographic improvement. Conclusion: Midfoot derotational osteotomy seems useful and has the possibility to be a definitive surgical procedure for ankylosing inversion deformity in patients with RA. Osteotomy should be performed from both medial and lateral sides, and careful retraction of soft tissues should always be kept in mind.